1994
DOI: 10.5636/jgg.46.669
|View full text |Cite
|
Sign up to set email alerts
|

The Low Energy Particle (LEP) Experlment onboard the GEOTAIL Satellite.

Abstract: The low energy particle (LEP) instrument onboard GEOTAIL is designed to make comprehensive observations of plasma and energetic electrons and ions with fine temporal resolution in the terrestrial magnetosphere (mainly magnetotail) and in the interplanetary medium. It consists of three units of sensors (LEP-EA, LEP-SW and LEP-MS) and a common electronics (LEP-E). The Energy-per-charge Analyzers (EA) measure three-dimensional velocity distributions of electrons (with EA-e) and ions (with EA-i), simultaneously an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
339
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 531 publications
(343 citation statements)
references
References 23 publications
4
339
0
Order By: Relevance
“…Figure 3a repeats the solar wind kinetic pressure of Figure 2 shifted 23 min to its Earth arrival time. The red traces in Figures 3b, 3c, 3d, 3f, 3g, and 3i correspond to plasma density, temperature, velocity, solar magnetospheric flow direction angles q and f, and plasma pressure, all measured by the Geotail LEP plasma experiment [Mukai et al, 1994] and shown at 12 s resolution. This experiment has separate instruments to measure the solar wind and the hot plasmas of the magnetosphere.…”
Section: Geotail Observationsmentioning
confidence: 99%
“…Figure 3a repeats the solar wind kinetic pressure of Figure 2 shifted 23 min to its Earth arrival time. The red traces in Figures 3b, 3c, 3d, 3f, 3g, and 3i correspond to plasma density, temperature, velocity, solar magnetospheric flow direction angles q and f, and plasma pressure, all measured by the Geotail LEP plasma experiment [Mukai et al, 1994] and shown at 12 s resolution. This experiment has separate instruments to measure the solar wind and the hot plasmas of the magnetosphere.…”
Section: Geotail Observationsmentioning
confidence: 99%
“…The 12 s resolution data from Geotail magnetometer [Kokubun et al, 1994] and the low-energy particle (LEP) experiment [Mukai et al, 1994] have been collected from 1998 to 2005. The LEP data on Geotail are over the energy range of several eV to 43 keV.…”
Section: Data Descriptionmentioning
confidence: 99%
“…From Geotail we use 12-sec averaged data from the Geotail magnetic field (Kokubun et al, 1994) and low energy particle experiment (Mukai et al, 1994).…”
Section: Introductionmentioning
confidence: 99%